Respostas
respondido por:
2
Olá!!!
Resolução!!!
PA :
an = a25 = 112
a1 = ?
n = 25
r = 8
Aplicando na fórmula
an = a1 + ( n - 1 ) • r
112 = a1 + ( 25 - 1 ) • 8
112 = a1 + 24 • 8
112 = a1 + 192
a1 + 192 = 112
a1 = 112 - 192
a1 = - 80
R = O primeiro termo da PA é - 80
Espero ter ajudado;!
Resolução!!!
PA :
an = a25 = 112
a1 = ?
n = 25
r = 8
Aplicando na fórmula
an = a1 + ( n - 1 ) • r
112 = a1 + ( 25 - 1 ) • 8
112 = a1 + 24 • 8
112 = a1 + 192
a1 + 192 = 112
a1 = 112 - 192
a1 = - 80
R = O primeiro termo da PA é - 80
Espero ter ajudado;!
respondido por:
2
an = a1 + ( n -1) . r
112 = a1 + ( 25 -1) . 8
112 = a1 + 192
112 - 192 = a1
a1 = -80
Helvio:
De nada.
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás